Borderland, Culture and Contestation between Nepal and India - Dhakal, Sedunath (KMC Research Journal, 2021)
The border between two countries is not only a passway to travel across, and legal trade transit; it is also the cause of socio-economic and cultural transmission, and sometimes it can also create political and criminal activities. This paper highlights how the border between Nepal and India has created contestation with different activities from the sociocultural celebration to the economic and political relations, and also to the terrorism and criminal activities. It traces historical contexts of setting the border in general, and the context of Nepal and India border in particular. The paper aims to describe the geographical, cultural, and socio-economic activities across the border. Based on the secondary materials available about open border, and its pros and cons, this paper focuses on the context of Nepal –India open border, its prospects and challenges for both countries. The analysis in this paper is based on books, documents, historical records about Nepal – Indian border, experiences of the people across the border and experts’ opinions from both countries.